Noise Levels Along the Palembang–Indralaya Highway (Jurnal Ilmu Kesehatan Masyarakat, 2019)
Palembang – Indralaya highway is a cross-provincial road where motor vehicle activity is constant, causing noise and affecting settlements along the road. Constant exposure to the noise that exceeds quality standards (55 dB) stipulated in Environmental Ministerial Decree (KEP.48/MENLH/11/1996), can cause a variety of health problems, such as hearing loss and psychological disorders. Therefore, this study is conducted to determine the noise level along the Palembang-Indralaya road. This study used an observational approach through direct observations and measurements using the Mini InScienPro SQ-100 sound level meter. The noise level is measured at two locations, i.e., on the curb and in houses located along the highway. Based on the observations and measurements, the highest noise intensity was during the daytime (78.0 - 102.4 dB). The highest intensity of noise inside and outside the house are 74 and 90 dB, respectively. This is due to the high volume and activity of vehicles crossing the highway. The intensity of the noise received by the residents along the highway is above the quality standards, so as to handle the noise, trees need to be planted around the housing (barrier plants). Keywords: Noise intensity, highway, sound level Meter